SELF DIGESTING: Dalam Kajian Tasawwuf atas Taklif Syariah - Ahmad Azaim Ibrahimy (LP2M Universitas Ibrahimy, 2013)
Every human being has the ability and potential which is different from one individual to another.Thepotential and the will be parsed and explored well if he is able to understand his identity.Contemplation is one approach to understand the self-concept, becauseit is actually anone’s attempt to do contemplation and concentration in doing the thinking intently. The state of concentration then becomes the expectation that he would be able to recognize his personality, potential, abilities, shortcomings, and soulcondition, so that when the all potential is able to be felt, it will eventually be easily managed to be positive energy.